1969
DOI: 10.1243/pime_proc_1969_184_035_02
|View full text |Cite
|
Sign up to set email alerts
|

High Strain Torsion Fatigue of Solid and Tubular Specimens

Abstract: A stress-strain history theory is developed for the entire life of solid cylinders subjected to reversals of torque under low-endurance fatigue conditions. Thin tubes and solid cylinders of a hot rolled mild steel are found to have identical stress range versus strain range relationships. However, fatigue behaviour is dependent on the stress field surrounding the crack initiation zone and hence the geometry of specimens has a most important effect in high strain fatigue processes. Cold drawn mild steel tubes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…They too found that cyclic softening occurred except at very low strains but like Wood and Segall they also found that when softening occurred this only followed a slight cyclic hardening in the first few cycles. Figs 8 and 9 illustrate the differences in cyclic and static behaviour for the En 32B material and a previously reported investigation with En 1B (34). These curves and those presented previously underline the inability of static tests to predict the behaviour of materials under cyclic conditions and designers are well advised to use cyclic characteristics instead.…”
Section: Cyclic Softening O R Hardeningmentioning
confidence: 55%
“…They too found that cyclic softening occurred except at very low strains but like Wood and Segall they also found that when softening occurred this only followed a slight cyclic hardening in the first few cycles. Figs 8 and 9 illustrate the differences in cyclic and static behaviour for the En 32B material and a previously reported investigation with En 1B (34). These curves and those presented previously underline the inability of static tests to predict the behaviour of materials under cyclic conditions and designers are well advised to use cyclic characteristics instead.…”
Section: Cyclic Softening O R Hardeningmentioning
confidence: 55%
“…Considering the specimen in the test is a solid round bar, the shear stress was calculated according to the slope of the T − γ hysteresis loop. This method was originally proposed by Miller and Chanlder, then Yang et al also presented a practical analysis for this equation. τ=12πR3[]3T+γdT, …”
Section: Materials and Experimentsmentioning
confidence: 99%
“…Here, the method proposed by Miller and Chandler (1970) approach and also used in (Brown, 1978;Lin et al, 1992) can be presented as:…”
Section: Stress Analysismentioning
confidence: 99%